CAMPUR KODE DALAM ACARA STAND UP COMEDY PALTV DI GRAND FINAL AUDISI PRESENTER PALTV 2017 - Fider Saputra (Universitas Aki, 2018)
Code mixing is a variation of language that we often hear in our dailylanguage life in various situations. The purpose of this research is to describe theform of code mixing used and to explain its usage function in Stand Up Comedyshow in grand final of presenter of PalTV 2017. This research type is descriptivequalitative research. Data collection techniques used are documentation and seenotes techniques. The results of this study show that there are 23 speechesindicated using mixed code in the form of words, phrases, clauses, abbreviations,and poem. Code mixing in the form of words are 20, in the form of phrases are 10(8 noun phrases, 1 adverbial phrase, and 1 verb phrase), in the form of clauseare 4, the abbreviation is 1, and the poem are 2. The function of mixing code is toconvince or to affirm something, to provide information, to increase prestige, togive an intellectual impression, to show knowledge, to adjust the topic of theevent, to show emotional situations, to emphasize things, to compare conditions,to attract attention, to invite others to do something, to invite laughter, to informdifferent conditions, to demonstrate ability, to be used as an opening, and to beused as the closing of an event.Keywords: Code mixing, words, phrases, clauses, abbreviations, poem.